Smoking cessation in dental setting: Effectiveness of behavioral therapy as well as patient’s and provider’s perception / Nurul Asyikin Yahya - Nurul Asyikin, Yahya (2017)
The objectives of this study were, 1) to assess the effectiveness of the 5A’s smoking cessation intervention (5A’s) to that of brief advice (BA) which dentists delivered in a dental setting; 2) To assess and compare the dental patients’ knowledge of the effects of smoking and perceptions on the role of dentists in smoking cessation intervention (SCI) by smoking status; 3) To assess smokers’ attitude towards smoking cessation counselling; 4) To investigate and compare the motivation for, capabilities in, and opportunities for SCI between private and public dentists; 5) To identify the barriers to implementing SCI in dental practice. Methods: Part 1 was a single-blinded randomized controlled trial was designed to compare the effectiveness of the 5A’s to that of BA. Six Dental Public Health specialists were recruited, randomized and trained to participate in this trial. Patients who fulfilled the inclusion criteria were enrolled into the assigned intervention programs. The main outcome measures were biochemically validated self-reported abstinence and behaviour change at 6-months follow-up. Part 2 comprised of 2 cross-sectional surveys using self-administered questionnaires conducted separately on dental patients and dentists’ population in Malaysia. Results: In the clinical trial, the odd of quitters in 5A’s intervention was 3.81 (95%CI: 1.871- 7.76; p= 0.00) times higher compared to BA. After controlling other factors, the odds ratio for the 5A’s was 1.90 (95%CI: 0.652-5.547; p=0.24) higher compared to BA. In the dental patient survey, there was a significant difference in the knowledge on effects of smoking among smokers and non-smokers (p<0.05). Commonly known effects of smoking were on stained teeth (n=335, 89.3%), bad breath (n=320, 85.3%), lung cancer (n=290, 77.3%) and oral cancer (n=279, 74.4%). Among smokers, majority (n=72, 81.8%) agreed on dentists giving advice on effects of smoking. Meanwhile, in the dentists’ survey, 285 dentists (public, n=158, 53.6%; private, n= 127, 43.1%) replied to the questionnaire survey. Statistically significant differences were found between the types of the dentist with their perceptions of their professional role and identity (p<0.05). A majority of public dentists (n=103, 65.1%) believed that promoting tobacco abstinence is an important part of their professional identity compared to private dentists (n=65, 51.2%). More public dentists (n=95, 60.1%) were significantly aware of the 5A’s guidelines compared to private dentists (n=34, 26.8%). Statistically significant differences were found between the types of dentists on their abilities to prevent patients from using tobacco products (p= 0.004). More of public dentists (n=77, 48.7%) were unsure they have the confidence compared to private dentists (n= 41, 32.3%). Conclusion: The 5A’s was found to be more effective in initiating positive behaviour change compared to BA. However, after controlling other factors, there was no difference in the effectiveness although the odds ratio was slightly higher in 5A’s. Dental patients have good knowledge of the effects of smoking on oral and general health and have positive perception about dentist giving smoking cessation counselling. Dentists whether in public or private practice have the motivation to conduct SCI; however, their capabilities are compromised and lack of support from their organisation.